Comparative study of the optical behavior of a porphyrin encapsulated in sol-gel silica coatings and in solution as a function of pH - Carmona, Noemi; Villegas, María Ángeles; García, Miguel; Llopis, José; Montero-Zeledón, Ernesto (Elsevier, 2016)
We report a comparative optical spectral study as a function of pH on a porphyrin encapsulated in a solgel matrix and in methanol solution. Its response has been discussed in terms of pH-sensitivity as a function of the coatings thickness. Comparison with the behavior of such porphyrin in methanol solution is also included. Optical properties of the porphyrin doped coatings show a quasi linear behavior throughout the pH range studied. Luminescent emission of doped coatings has its maximum peak at a slightly lower wavelength compared with the response in liquid medium (methanol solution), while in the excitation spectra no clear tendency was observed for different pH. Coatings doped with 1 wt% porphyrin fulfill Lambert-Beer law, although the molar absorptivity of the encapsulated porphyrin in the coatings is slightly lower than in methanol solution.
Artículo científico
Keywords: Revestimientos; Propiedades ópticas; Sensibilidad; Ácidez; Research Subject Categories::NATURAL SCIENCES::Chemistry::Physical chemistry::Chemical physics